POTRET IDEAL KEPEMIMPINAN PEREMPUAN SEBAGAI PENGELOLA LEMBAGA PAUD - Wiyani, Novan Ardy (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
This paper is intended to describe the ideal portrait of women’s leadership in managing early childhood institutions. There are eight characteristics of the ideal figure of woman leaders, as follows: 1) confident and having high idealism, 2) persistent and having ability to build a team work, 3) simple and humble, 4) wise in making a decision, 5) independent, 6) credible, 7) protecting, and 8) inspirational and can be a model.